The role of marketing Ambidexterity in Achieving strategic success - Hind Naeem Hoshi (Zien Journals, 2025)
The current research seeks to know the role of marketing Ambidexterity in achieving strategic success, by relying on a modern marketing tool that keeps pace with the emerging changes in the external environment, based on two variables: the independent variable (marketing Ambidexterity) with its dimensions (exploring opportunities, exploiting opportunities) and the dependent variable (strategic success) with its dimensions (growth, adaptation, specific strategy), where a sample consisting of (84)From the administrative leadership at the University of Maysan, The research reached a set of conclusions, including (from the results of the statistical analysis, it shows the clear interest of the research sample in marketing ingenuity Far away(Exploring opportunities, exploiting opportunities), because they are the basis for its survival in the competitive environment and building a solid base that attracts different categories of students and teaching staff, because searching for opportunities and exploiting them adds additional strength to the sample being studied and strengthens its position in a manner that is consistent with the labor market.)And the recommendations include:( Increase focus and interest in marketing Ambidexterity in order to achieve excellence in the field of providing educational services and overcome competitors by exploring and exploiting everything new in the field of education in a way that ensures the strategic success of the sample studied in the long term
Keywords: Marketing Acumen; Exploring Opportunities; Exploiting Opportunities